Initiation and decision-making of joint activities within peer interaction in student-centred mathematics lessons. Issue 4 (2nd October 2021) - Kämäräinen, Anniina; Eronen, Lasse; Björn, Piia M.; Kärnä, Eija
ABSTRACT: This study describes how students initiate and manage transitions between activities during group-work. Audio and video recordings were collected in secondary school mathematics lessons (6 x 75 min) based on student-centred learning and the idea of minimal teacher instruction. In these lessons, the students were given the responsibility to initiate and direct their own activities. Drawing on conversation analysis, the study focused on explicating a) two alternative initiating action formats: proposal and announcement, b) the co-participants' responses and c) how these turns influence the nature of decision-making and subsequent group-work. The findings showed that joint activities were typically initiated through proposals formulated in interrogative or declarative construction. These equal ways of directing co-participants called for shared decision-making. If the proposal was followed by explicit or implicit resistance, the students used various verbal, embodied and material resources to engage the co-participant in negotiating and aligning with the proposed activity. Further, these sequences generally led to a collaborative working mode. By contrast, announcement was based on the initiator's decision, and these sequences led to a guided working mode structured by the initiator. The findings extend our understanding of how a group of students coordinate transitions between activities.